2015
DOI: 10.11607/jomi.3487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Three-Dimensional Accuracy of Implant Impression Techniques in Two Simulated Clinical Conditions by Optical Scanning

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…In the present study, the conventional cast group was produced by a protocol similar to other studies that reported minimal deviations when using open tray splinted impression technique, polyether impression materials and type IV low expansion stone (Papaspyridakos et al, ). Nonetheless, the 3‐D implant deviations of conventional casts were slightly higher in this study with mean deviation of 53.49 μm compared to another study which reported mean deviation of 29.8 μm (Sabouhi, Bajoghli, & Abolhasani, ). This could be due to multiple differences between the two studies, such as operator technique, master cast undercuts, difference in implants angulation and implant position within the dental arch.…”
Section: Discussioncontrasting
confidence: 85%
“…In the present study, the conventional cast group was produced by a protocol similar to other studies that reported minimal deviations when using open tray splinted impression technique, polyether impression materials and type IV low expansion stone (Papaspyridakos et al, ). Nonetheless, the 3‐D implant deviations of conventional casts were slightly higher in this study with mean deviation of 53.49 μm compared to another study which reported mean deviation of 29.8 μm (Sabouhi, Bajoghli, & Abolhasani, ). This could be due to multiple differences between the two studies, such as operator technique, master cast undercuts, difference in implants angulation and implant position within the dental arch.…”
Section: Discussioncontrasting
confidence: 85%
“…Twelve studies with partially edentulous arches had specimens with one implant (one study), two implants (eight studies) and with two and five implants, respectively (one study). Two studies included partially and completely edentulous arches (Sabouhi, Bajoghli, & Abolhasani, ; Sabouhi, Bajoghli, Dakhilalian, Beygi, & Abolhasani, ), one study included completely edentulous arches and a single‐unit restoration (Abdel‐Azim et al., ). Two studies assessed a single unit (Aktas et al., ; Lee, Betensky, Gianneschi, & Gallucci, ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies of conventional implant impressions (55 studies) did not examine the vertical position of implants. The equigingival (BalaMurugan & Manimaran, ) or supragingival (Sabouhi et al., , ) placement of implants was stated, however, not evaluated for the impression accuracy. Implants were placed at depths of 0, 1 and 3 mm and examined along with other specifications for conventional implant impressions (Martínez‐Rus et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…This may or may not be a factor in the final restoration but during initial healing the one piece screw‐retained provisional may play a pivotal role in optimal tissue healing and preservation. Currently available CAD/CAM software allows the clinician to evaluate the existing bony architecture and anatomical dimensions of the tooth before extraction, and then fabricate an ideal provisional matrix that duplicates the natural anatomy . This critical sub‐gingival restorative abutment interface is a separate and defined aspect to the supra‐gingival esthetics and functional aspects of the coronal aspect of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available CAD/ CAM software allows the clinician to evaluate the existing bony architecture and anatomical dimensions of the tooth before extraction, and then fabricate an ideal provisional matrix that duplicates the natural anatomy. [34][35][36][37] This critical sub-gingival restorative abutment interface is a separate and defined aspect to the supra-gingival esthetics and functional aspects of the coronal aspect of the restoration. All the original data acquired is used by the laboratory in conjunction with the gingival displacement formula in designing the optimal submergence and emergence profiles of the abutment relative to the gingival collar and separate crown.…”
Section: Discussionmentioning
confidence: 99%